Inflation and Economic Activity in Suriname - Gavin Ooft (Centrale Bank van Suriname, 2016)
Maintaining a low rate of inflation and sustainable economic growth are at the core of monetary policymaking. Price stability is considered a condition for a healthy macroeconomic environment which promotes sustainable growth and a low rate of inflation is necessary to maintain stability in the financial sector as well as to boost investment activities. Motivated by the largely-discussed relationship between inflation and output, this paper examines this relationship for the economy of Suriname over the period 1975 to 2015, utilizing a vector autoregressive model and impulse response functions. The findings of the study reveal how the various sources of inflation impact on the economy of Suriname. Domestic price shocks and money-supply shocks, in particular, seem to substantially impact on economic activity. Exchange-rate shocks are detrimental to domestic prices. Based on the findings of this study, it is highly recommended for the Central Bank of Suriname to continue its prudent monetary policies in order to maintain a stable exchange rate and price stability. The study advocates for maintaining a healthy macroeconomic climate with price stability, which is a crucial condition for Suriname to follow a sustained path for economic growth and development.
Additional information: The author is a staff member of the Research Department of the Central Bank of Suriname. The views expressed in this paper are those of the author and do not necessarily reflect those of the Bank. Research papers constitute work in progress and are published to elicit comments and to further debate.
Keywords: E31; O42; C21; 330; Inflation; Economic Growth; Vector Autoregression; Impulse Response Functions